Pengaruh Tingkat Pemahaman Riba terhadap Praktik Utang Piutang Pedagang di Pasar Kordon Kujangsari Kota Bandung - Iin Safariah; Sri Jubaida Arifin (Penerbit Jurnal Indonesia, 2026)
This study examines the effect of traders’ understanding of riba on debt–credit behavior at Pasar Kordon Kujangsari, Bandung City, while also describing the level of traders’ knowledge and the conformity of debt practices with Sharia principles. The analysis focuses on the relationship between Islamic financial literacy and traders’ economic behavior, considering that debt transactions remain essential for sustaining micro-enterprises in traditional markets. The research adopts a quantitative approach using a survey method, with primary data collected through a five-point Likert-scale questionnaire administered to 66 traders selected randomly from a population of 190 using the Slovin formula at a 90 percent confidence level. Data analysis was conducted using SPSS version 29 through validity and reliability tests, classical assumption tests, simple linear regression, and hypothesis testing. The results indicate that traders’ knowledge of riba is at a moderately high level and that their debt–credit behavior is relatively positive. Regression analysis confirms a positive and significant effect of riba understanding on debt behavior, with a regression coefficient of 0.162, a significance value of 0.005, and a coefficient of determination (R²) of 0.117, underscoring the importance of strengthening Islamic financial literacy and support for Sharia-compliant financing in traders’ economic practices.